Chronic Prurigo of Nodular Type: A Review - Claudia Zeidler; Athanasios Tsianakas; Manuel Pereira; Hartmut Ständer; Gil Yosipovitch; Sonja Ständer (Medical Journals Sweden, 2017)
Prurigo nodularis (PN) is a subtype of chronic prurigo presenting single to multiple symmetrically distributed, hyperkeratotic and intensively itching papules and nodules. PN evolves along with chronic pruritus in the context of diverse dermatological, systemic, neurological or psychiatric conditions. Permanent scratching is possibly a major trigger of PN, although its exact pathophysiology remains unclear. Current state-of-the-art therapy for PN consists of topical steroids, capsaicin, calcineurin inhibitors, ultraviolet (UV) therapy, systemic administration of gabapentinoids, μ-opioid receptor antagonists, antidepressants or immunosuppressants. Novel treatment concepts, such as inhibitors of neurokinin-1, opioid and interleukin-31 receptors, have been developed and are currently being clinically tested.